2019
DOI: 10.1530/eje-19-0259
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic medication and risk of dementia in patients with type 2 diabetes: a nested case–control study

Abstract: Objective Diabetes is a risk factor for dementia, but whether antidiabetic medication decreases the risk is unclear. We examined the association between antidiabetic medication and dementia. Design We performed a nested case–control study within a cohort of all 176 250 patients registered with type 2 diabetes in the Danish National Diabetes Register between 1995 and 2012. This population was followed for dementia diagnosis or anti-dementia medication use until May 2018. Using risk-set sampling, each dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
117
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 29 publications
4
117
2
6
Order By: Relevance
“…Our results demonstrated that the types of DPP-4i had a class effect on dementia prevention, with a main focus on vascular dementia, but not on AD. These results were not consistent with those of previous human studies [21,22,26]. The discrepancy among the studies may be attributed to the populations and numbers of the study participants, study designs, durations of follow up, and end points of the studies (cognition and dementia definitions and types).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Our results demonstrated that the types of DPP-4i had a class effect on dementia prevention, with a main focus on vascular dementia, but not on AD. These results were not consistent with those of previous human studies [21,22,26]. The discrepancy among the studies may be attributed to the populations and numbers of the study participants, study designs, durations of follow up, and end points of the studies (cognition and dementia definitions and types).…”
Section: Discussioncontrasting
confidence: 90%
“…The latest nested case control study from a cohort of 176,250 patients registered in the Danish National Diabetes Register study showed that the use of DPP-4i in T2D patients significantly decreased the risk of dementia compared to in non-DPP-4i users during a long duration of follow up (7.2 years). However, this study did not reveal the effect of DPP-4i on different types of dementia [26].…”
Section: Discussioncontrasting
confidence: 73%
“…12 The DPP4 inhibitors can affect systems unrelated to GLP1, 26 and therefore further studies would be needed to understand the mechanism(s) of action relevant to memory, and to determine whether the GLP1 receptor agonists (incretins) would be equally beneficial. 32 We did not assess relationships between insulin use and memory because insulin is likely to reflect longer duration of diabetes, resulting in a considerably different propensity to receive insulin therapy leading to confounding by indication. Instead, insulin use was controlled for in the analyses.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4i increases the glucose-dependent insulin response and reduces glucagon secretion by inhibiting GLP-1 degradation [28]. Wium-Andersen, et al showed DPP-4i ever-users had a lower odds of dementia than never-users (OR= 0.80, 95% CI 0.74-0.88) and the Met + DPP-4i dual combination was associated with a lower odds of dementia than no anti-diabetes medication (OR = 0.70, 95% CI 0.58-0.86) [20]. In subclasses of dementia, Kim, et al demonstrated that DPP-4i new users versus SU new users over 60 years old had a lower risk of all-cause dementia and AD (HR = 0.66, 95% CI 0.56-0.78 and HR = 0.64, 95% CI = 0.52-0.79), but not VaD (HR = 0.56, 95% CI 0.38-1.14) over 4 years [14].…”
Section: Discussionmentioning
confidence: 99%
“…In combination with Met, Lu et al reported that 204,323 Taiwan patients with T2D and ≥ 65 years that MET + TZD was signi cantly superior to Met + SU in the risk of developing dementia (HR = 0.56) [15]. On the other hand, a nationwide nested case-control study, enrolled from 1995 to 2012, reported that TZD ever-users, including rosiglitazone, versus never-users did not have a signi cant odds of developing dementia (OR = 0.89, 95% CI 0.76-1.03), but further analysis of dual therapy with TZD was not conducted [20]. In Korea, there are two TZDs, lobeglitazone and pioglitazone, approved by the Ministry of Food and Drug Safety.…”
Section: Discussionmentioning
confidence: 99%